When Should Central Banks Fear Inflation Expectations? - Lucio Gobbi; Ronny Mazzocchi; Roberto Tamborini (Center for Economic Studies and ifo Institute (CESifo), 2024)
When inflation picks up, central banks are most concerned that the de-anchoring of inflation expectations and the ignition of wage-price spirals will trigger inflation dynamic instability. However, such scenarios do not materialize in the standard New Keynesian theoretical framework for monetary policy. Using a simulative model, we show that they can materialize upon introducing in particularly strong doses boundedly-rational expectations that de-anchor endogenously, as they are updated according to the actual inflation process, with indexed wages, and persistent inflation shocks. In these cases, a more hawkish central-bank stance on inflation expands the stability region of the system, which however remains bounded. On the other hand, the critical combinations of factors that trigger instability can be regarded as extreme in empirical terms, while in "normal times" the system is resilient to shocks and expectation de-anchoring even with more dovish monetary policy.
Keywords: E17; E30; E50; 330; cost-push inflation; New Keynesian models for monetary policy; wage-price spiral; de-anchoring of inflation expectations